Human Resources Continuous Improvement Performance Model dan Recognition & Reward Scheme: A Case Study - Derried Anwar; Siana Halim (Jurnal Titra, 2016)
Continuous Improvement (CI) in PT. X’s Human Resources (HR) department has already been started for almost 2 years. However, HR didn’t have any mechanism to measure how good a department in doing CI. Moreover, a new way to increase employees’ spirit to contribute in CI by creating improvement ideas is also needed. HR CI Performance Model and Recognition & Reward Scheme are created as a measurement mechanism and to boost up CI spirit in HR. HR CI Performance Model is developed until two times to describe the current condition more appropriately. Recognition & Reward Scheme is created by Balance Scorecard theory. Both of these measurements can increase the amount of created improvement ideas by 25.3% and department participation by 22%. Additionally, some of managers and staffs also acknowledge the positive impacts of both of those measurements.